La RSE entre discours et éthique. Cas d’une station balnéaire présumée durable : Taghazout Bay, Maroc - Hassan Faouzi; Mohamed Ait Nacer (Belgeo)
Today we are witnessing a resurgence of discourse on Corporate Social Responsibility (CSR). This topic has been widely debated over the last decades and its institutionalization is becoming more and more popular in the tourism sector. In Morocco, where tourism activity plays an important role in the economy, tourism establishments are called upon to comply with new requirements for sustainable tourism. This article examines the relationship between the discourse and the effectiveness of CSR approaches in Moroccan hotels through the resort of Taghazout Bay, Agadir.